PENGARUH KOMPETENSI APARATUR PEMERINTAH DAERAH, PENERAPAN AKUNTABILITAS KEUANGAN, PEMANFAATAN TEKNOLOGI INFORMASI, DAN KETAATAN PADA PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) - Egrinaen Mauliziska Nugraheni; Amries Rusli Tanjung; Susilatri - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to observe the effect of the competence of local government officials, the application of financial accountability, utilization of information technology and compliance with regulations on performance accountability of government agencies (AKIP). The sample used in this study is the Head of Department, Chief Financial Officer, and Chief Financial sub-sections contained in 29 SKPD’s Pekanbaru City. Analysis of research on is use of multiple linear regression equation is with SPSS (Statistical Product and Service Solutions). The result showed competence of the Local Government Reform affect the performance of Local Government Agencies. Applications of Financial Accountability affect the performance of Local Government Agencies. Utilization of Information Technology has no effect on the Performance of Local Government Agencies. Adherences to Laws do not affect the performance of Local Government Agencies.Keywords: Competence of the Local Government Reform, Applications of Financial Accountability, Utilization of Information Technology, Adherences to Laws, performance of Local Government Agencies.